EDUCATIONAL INTERVENTION IN THE POST-OPERATIVE PERIOD OF CARDIAC SURGERY: A MIXED METHODS STUDY GUIDED BY THE HEALTH BELIEF MODEL. - Paz, Vanêssa Piccinin; Kolankiewicz, Adriane Cristina Bernat; Nogueira, Luciana de Alcantara; Miranda, Fernanda Moura D'Almeida; Mantovani, Maria de Fátima; Lorenzini, Elisiane (Texto & Contexto Enfermagem, 2025)
Objective: to analyze the contribution of educational intervention to health literacy and knowledge of coronary artery disease in adults in the late postoperative period of cardiac surgery; and to understand the factors which affect behavior change based on a theoretical model. Methods: this is a mixed-methods study with educational intervention based on the health belief model, conducted with 25 people undergoing cardiac surgery living in Western Paraná, Brazil. Data were collected from June 2021 to October 2022. A sociodemographic-clinical questionnaire and the Coronary Artery Disease Education Questionnaire Short-Version and Eight-item Health Literacy Assessment Tool instruments were used in the quantitative stage, analyzed using descriptive and inferential statistics. Then, a semi-structured interview was conducted in the qualitative stage, investigated by content analysis. A joint display approach based on the belief model was chosen for data integration. Results: the intervention enabled an increase in health literacy (p=0.035) and knowledge about the disease (p=0.007). The qualitative analysis generated the following categories: before the intervention: "Susceptibility", "Severity" and "Perceived severity"; after the intervention: "Perceived benefits" and "Barriers encountered in rehabilitation". Data integration enabled identifying perceptions before and after the intervention, modifying factors, benefits and barriers encountered. Conclusion: there was an increase in knowledge about the disease and health literacy through developing self-management skills. The use of tools to assess knowledge about the disease and health literacy enabled planning educational actions to fill existing gaps.